Estudio de factibilidad para la creación de una empresa de productos en madera plástica elaborados a partir de residuos plásticos y residuos de madera en la ciudad de Bogotá (2021)
The main objective of this project is to carry out a feasibility study for the creation of a plastic wood company in the city of Bogotá. It is carried out due to the need to collaborate with the environment, the shortage of products made with this type of material, since it is an industry that is growing in many other countries. Several and different studies were carried out, in which it was evidenced that it is a well-received product and that they are willing to acquire, where the needs to make this product were also found, whether in area, equipment and money, and with respect to the laws necessary for a project of this type including environmental legal regulations. It was financially determined that the project over 3 years is not profitable since it is difficult to emerge in this industry with all the expenses incurred and the little recognition with which it starts. However, it was observed, based on its growth, that from the 4th year onwards the investment was recovered, therefore after 5 years this project becomes profitable and economically efficient.